Formal microcredit and the sustainability of Peruvian microenterprises. Lima Case - Mauricio Pachas, Pablo Willins (2021)
It is of public knowledge that Lima has experienced an immigration phenomenon predominantly since the 70’s, evidenced by a disorderly demographic explosion, where the population of lesser resources has found in popular entrepreneurship, option for self-employment and improve their economic income and access to better quality of life, creating micro enterprises. The formal microcredit appeared as a form of mutual support, between the contributing and the receiving entity. This research, with a quantitative approach, applied type, relational level, non-experimental design and cross section, sought to determine the relationship between formal microcredit and the sustainability of Peruvian microenterprises, in the case of Metropolitan Lima, 2020. Descriptive, dispersion, normality and hypothesis testing results were obtained. The results showed that formal microcredit is positively and moderately related to the sustainability (general, environmental, social and economic) of Peruvian microenterprises, specifically in Lima, 2020. Finally, recommendations are presented to government representatives and decision-makers, to managers of companies in the banking sector and to researchers specializing in this area.